2022
DOI: 10.1021/acs.inorgchem.2c00965
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Precise Platinum Carbonyl Nanoclusters: Synthesis, Total Structure, and Electrochemical Investigation of [Pt27(CO)31]4– Displaying a Defective Structure

Abstract: The molecular Pt nanocluster [Pt 27 (CO) 31 ] 4– ( 1 4– ) was obtained by thermal decomposition of [Pt 15 (CO) 30 ] 2– in tetrahydrofuran under a H 2 atmosphere. The reaction of 1 4– with increasing amounts of HBF 4 · Et 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In many cases, we observed that the voltammetric profiles of clusters are ill defined at Pt electrodes, while more resolved peaks are instead obtained at GC. 31,53 In Fig. S24 in the ESI, † the CV responses of [Pt 19−x Ni x (CO) 22 ] 4− (x = 3.11) at the two electrodes are compared.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…In many cases, we observed that the voltammetric profiles of clusters are ill defined at Pt electrodes, while more resolved peaks are instead obtained at GC. 31,53 In Fig. S24 in the ESI, † the CV responses of [Pt 19−x Ni x (CO) 22 ] 4− (x = 3.11) at the two electrodes are compared.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…These electrochemical methods have also been applied to Au NCs protected by phosphine 121–128 and stibine, 129 and to NCs based on Ag, 130–133 Cu, 134 and group 10 elements. 135–139 In the future, these electrochemical techniques are expected to reveal the electronic states of metal NCs protected by other ligands and composed of other metals. 140–144…”
Section: Discussionmentioning
confidence: 99%
“…Compared with [Au 25 (SC 6 H 13 ) 18 ] − , the oxidation and reduction peaks (O1 and R1) of [Au 25 (PPh 3 ) 10 (SC 6 H 13 ) 5 Cl 2 ] 2+ were observed at significantly These electrochemical methods have also been applied to Au NCs protected by phosphine [121][122][123][124][125][126][127][128] and stibine, 129 and to NCs based on Ag, [130][131][132][133] Cu, 134 and group 10 elements. [135][136][137][138][139] In the future, these electrochemical techniques are expected to reveal the electronic states of metal NCs protected by other ligands and composed of other metals. [140][141][142][143][144] The electrochemical gap also varies depending on the ligand, solvent, electrolyte, measurement mode, temperature, and other factors.…”
Section: Size Effect On the Electronic Structure Of Thiolateprotected...mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In this respect, molecular clusters and nanoclusters represent a link between metal complexes and metal nanoparticles. [12][13][14][15][16][17][18][19][20][21] Molecular clusters may be used in homogenous catalysis or as precursors of supported heterogeneous nanostructured catalysts. [22][23][24][25] [Ru 3 Ir(CO) 13 ] À showed high catalytic activity for the carbonylation of methanol.…”
Section: Introductionmentioning
confidence: 99%
“…1–11 In this respect, molecular clusters and nanoclusters represent a link between metal complexes and metal nanoparticles. 12–21 Molecular clusters may be used in homogenous catalysis or as precursors of supported heterogeneous nanostructured catalysts. 22–25…”
Section: Introductionmentioning
confidence: 99%